Research progress on flexible oxide-based thin film transistors - Zhang, Lirong (2019)
Oxide semiconductors have drawn much attention in recent years due to their outstanding electrical performance, such as relatively high carrier mobility, good uniformity, low process temperature, optical transparency, low cost and especially flexibility. Flexible oxide-based thin film transistors (TFTs) are one of the hottest research topics for next-generation displays, radiofrequency identification (RFID) tags, sensors, and integrated circuits in the wearable field. The carrier transport mechanism of oxide semiconductor materials and typical device configurations of TFTs are firstly described in this invited review. Then, we describe the research progress on flexible oxide-based TFTs, including representative TFTs fabricated on different kinds of flexible substrates, the mechanical stress effect on TFTs and optimized methods to reduce this effect. Finally, an outlook for the future development of oxide-based TFTs is given.